Vascular impulse technology versus elevation for reducing the swelling of upper and lower extremity joint fractures - Barbari, Jan el; Schnetzke, Marc; Bergmann, Moritz; Baumann, Lukas; Vetter, Sven Y.; Swartman, Benedict; Grützner, Paul Alfred; Franke, Jochen (Scientific reports, 2023)
Soft-tissue conditioning due to posttraumatic oedema after complicated joint fractures is a central therapeutic aspect both pre- and postoperatively. On average, 6-10 days pass until the patient is suitable for surgery. This study compares the decongestant effect of vascular impulse technology (VIT) with that of conventional elevation. In this monocentric RCT, 68 patients with joint fractures of the upper (n = 36) and lower (n = 32) extremity were included and randomized after consent in a 1:1 ratio. Variables were evaluated for all fractures together and additionally subdivided into upper or lower extremity for better clinical comparability. Primary endpoint was the time in days from hospital admission to operability. Secondary endpoints were total length of stay, oedema reduction, pain intensity, complications, and revisions. The time from admission until operability was reduced by 1.4 (95% CI − 0.4; 3.1) days in the mITT analysis (p = 0.120) and was statistically significant with 1.7 (95% CI 0.1; 3.3) days in the as-treated sensitivity analysis (pAT = 0.038). Significantly less pain and a faster oedema reduction were found in the intervention group. Due to rare occurrences, nothing can be concluded regarding complications and revisions. Administration of VIT therapy did not lead to a significant reduction in time until operability in the whole population but was superior to elevation for soft-tissue conditioning and pain reduction. However, there was a significant reduction by 2.5 days (95% CI 0.7; 4.3) in the subgroup of lower extremity fractures. VIT therapy therefore seems to be a helpful tool in the treatment of posttraumatic oedema after complex joint fractures of the lower and upper extremity, especially in tibial head and lower leg fractures.
Gesehen am 25.05.2023